Pencegahan Bullying Melalui Literasi Media Di Kalangan Gen Z - Chotijah Fanaqi; Ardli Swardana; Nur Asifa; Dhea Nasywa Haura (Jurnal Media Pengabdian Komunikasi, 2026)
Abstract Bullying remains a serious issue in Indonesia’s educational environment, including among Generation Z adolescents who are deeply immersed in digital technology. Data from the National Survey on the Life Experiences of Children and Adolescents (SNPHAR) conducted by the Ministry of Women’s Empowerment and Child Protection (2018) shows that two out of three children aged 13–17 have experienced at least one form of violence. This situation underscores the urgency of bullying prevention efforts, particularly through a digital media literacy approach tailored to the characteristics of Gen Z. This Community Service (PKM) activity aims to raise awareness among students at MTs Persis 101 Sukarendah, Pangatikan Subdistrict, Garut, regarding the dangers of bullying and to equip them with digital media literacy skills. The activity’s methodology comprised three stages: preparation (identifying partner needs, developing materials, and coordinating with the school); implementation (screening an educational film, presenting materials by guest speakers, and conducting interactive discussions); and evaluation (reflections by students and the PKM team). The results of the activity showed that students gained a better understanding of the types, impacts, and causes of bullying. The film screening successfully fostered empathy, the materials reinforced cognitive knowledge, and the interactive discussions encouraged active student participation. Some students expressed a commitment to not engage in bullying and to courageously report any incidents that occur. The film screening successfully fostered empathy, the educational materials reinforced cognitive knowledge, and the interactive discussions encouraged active student participation. Some students expressed a commitment to refrain from bullying and to courageously report any incidents that occur. The evaluation also confirmed that the combined approach of film, educational materials, and discussion is effective in raising awareness and changing students’ attitudes. The main contribution of this PKM lies in strengthening digital media literacy as a strategy for preventing bullying among Gen Z, as well as fostering a commitment on the part of schools to create a safe, inclusive, and bullying-free environment. Keywords: Bullying prevention; digital media literacy; Generation Z; inclusive education.J Abstrak Bullying masih menjadi salah satu persoalan serius di lingkungan pendidikan Indonesia, termasuk di kalangan remaja Generasi Z yang sangat dekat dengan teknologi digital. Data Survei Nasional Pengalaman Hidup Anak dan Remaja (SNPHAR) Kementerian Pemberdayaan Perempuan dan Perlindungan Anak (2018) menunjukkan bahwa dua dari tiga anak berusia 13–17 tahun pernah mengalami sedikitnya satu bentuk kekerasan. Kondisi ini menunjukkan urgensi upaya pencegahan bullying, khususnya dengan pendekatan literasi media digital yang relevan bagi karakteristik Gen Z. Kegiatan Pengabdian Kepada Masyarakat (PKM) ini bertujuan untuk meningkatkan kesadaran siswa MTs Persis 101 Sukarendah, Kecamatan Pangatikan, Garut, mengenai bahaya bullying serta membekali mereka dengan keterampilan literasi media digital. Metodologi kegiatan mencakup tiga tahap, yaitu persiapan (identifikasi kebutuhan mitra, penyusunan materi, dan koordinasi sekolah), pelaksanaan (pemutaran film edukatif, penyampaian materi oleh narasumber, dan diskusi interaktif), serta evaluasi (refleksi siswa dan tim PKM). Hasil kegiatan menunjukkan bahwa siswa memperoleh pemahaman yang lebih baik tentang jenis, dampak, dan faktor penyebab bullying. Pemutaran film berhasil membangun empati, materi memperkuat pengetahuan kognitif, dan diskusi interaktif mendorong partisipasi aktif siswa. Sebagian siswa menyatakan komitmen untuk tidak melakukan perundungan dan berani melaporkan kasus yang terjadi. Evaluasi juga menegaskan bahwa metode kombinasi film, materi, dan diskusi efektif dalam meningkatkan kesadaran dan perubahan sikap siswa. Kontribusi utama PKM ini terletak pada penguatan literasi media digital sebagai strategi pencegahan bullying di kalangan Gen Z serta pembentukan komitmen sekolah dalam menciptakan lingkungan yang aman, inklusif, dan bebas perundungan. Kata-kata kunci: Pencegahan bullying; literasi media digital; generasi z; pendidikan inklusif.